Thalidomide reduces tumour necrosis factor α and interleukin 12 production in patients with chronic active Crohn's disease. Issue 2 (1st February 2002) - Bauditz, J; Wedel, S; Lochs, H
Abstract : Background: Thalidomide improves clinical symptoms in patients with therapy refractory Crohn's disease, as shown in two recent studies. The mechanism of this effect however is still unknown. Suppression of tumour necrosis factor α (TNF-α) by thalidomide has been suggested as a possible mechanism. However, effects on other cytokines have not been adequately investigated. Aim: The aim of our study was to investigate the effects of thalidomide on cytokine production in patients with inflammatory bowel disease (IBD). Methods: Ten patients with therapy refractory IBD (nine Crohn's disease, one ulcerative colitis) received thalidomide 300 mg daily in a 12 week open label study. Production of TNF-α, interleukin (IL)-1β, IL-6, and IL-12 was investigated in short term cultures of stimulated colonic lamina propria mononuclear cells (LPMC) and peripheral blood monocytes (PBMC) before and after 12 weeks of treatment. LPMC were also cultured with graded doses of thalidomide. Results: Three patients discontinued treatment because of sedative side effects. In the other patients, disease activity decreased significantly, with four patients achieving remission. Production of TNF-α and IL-12 decreased during treatment with thalidomide: LPMC (TNF-α: 42.3 (8.3) pg/ml v 16.4 (6.3); IL-12: 9.7 (3.3) v 5.0 (2.5); p<0.04) and PBMC (TNF-α: 62.8 (14.6) v 22.5 (9.2); p<0.02). Production of IL-1β and IL-6 did not change significantly. Culturing of LPMC with thalidomide showed a dose dependent decrease in TNF-α and IL-12 production. Conclusion: The clinical effects of thalidomide in Crohn's disease may be mediated by reduction of both TNF-α and IL-12.